Clinical profile of thrombocytopenia in pediatric patients - Chauhan, Anuya V.; Mehta, Disha A.; Patel, Urvi (International Journal of Contemporary Pediatrics, 2024)
Background: Thrombocytopenia is often asymptomatic and may present as an incidental finding during routine evaluation or during laboratory investigations performed for other reasons. Most common immune mediated cause of thrombocytopenia in children is immune thrombocytopenic purpura. Early diagnosis and treatment is guided by the severity and specific cause of the disease. Methods: This prospective study included all the admitted patients between >1 month to <12 years of age confirmed as having thrombocytopenia with platelet count <1,50,000/micro-litre by laboratory methods. Detailed history regarding various symptoms of onset and progression was recorded. Data of this study was recorded in Microsoft Excel and analyzed using statistical method. Results: This study included 120 patients with thrombocytopenia. Incidence of thrombocytopenia among hospital admission was 4.3%. Male to female ratio was 1.6:1. 55 (45.8%) patients were more than 5 years, 26 (21.67%) patients were between 3-5 years, 28 (23.33%) patients were between 1-3years, 11 (9.17%) were infants. 112 (99.2%) patients presented with fever while 81 (67.5%) patients had vomiting. Bleeding from any site and petechiae, purpura as a presenting complaint was seen only in 7 (5.8%) and 6 (5%) respectively. 24 patients received blood products. Conclusions: Infectious diseases were the most common cause of thrombocytopenia in children particularly moderate thrombocytopenia in present study. Thrombocytopenia is a common hematological finding in many febrile illnesses like dengue, malaria. Fever, vomiting were more significant symptoms. Symptomatic and supportive treatment in form of intravenous fluids and antipyretics were required in most of the children. Very few patients required platelet rich concentrate (PRC) for treatment.